Multifunctional Performance of Bio-Based Polyurethane Composites Reinforced with Graphene Oxide Nanoparticles - Muhammad Abdurrahman, Munir; Fitria, Rahmawati; Ahlam, Inayatullah; Sofian, Ibrahim (Forester. Forester Communications Inc. Ltd., 2026)
The development and multifaceted efficacy of bio-based polyurethane composites reinforced with graphene oxide (GO) nanoparticles are described in this study. Polyol produced from palm kernel oil combined with methylene diphenyl diisocyanate to fabricate polyurethane (PU), which provides a sustainable basis for cutting-edge functional materials. To improve the PU properties, GO was used at various concentrations (1, 2, 5, and 10%) using a sonication-assisted solution casting method. Fourier Transform Infrared Spectroscopy (FTIR) was applied to verify the urethane linkages and the disappearance of isocyanate structure, and it demonstrated satisfactory molecular compatibility by revealing hydrogen-bonding interactions between the GO functional groups and PU chains. At the higher loadings of GO, the Field Emission Scanning Electron Microscopy (FESEM) exhibited uniform GO dispersion throughout the matrix with little agglomeration. TGA and DSC were employed to study the thermal properties of PU and PU/GO, and they demonstrated a definite improvement in thermal stability, where PU/GO showed a delayed degradation initiation, and improved char production at higher levels of GO. A stable matrix structure and limited polymer chain mobility were further investigated by DSC. The conductivity of PU/GO was confirmed by electrochemical impedance spectroscopy (EIS) to study the synergistic electron-ion transport, showing a significant decrease in bulk and charge-transfer resistances with increasing GO levels. The addition of GO improved the insulating bio-based PU into an electroconductive and thermally stable composite that could be considered for flexible electronics, protective coatings, and bioelectronic devices, where the PU/GO materials offer a high-performing and sustainable alternative.